Optimized compensation based on linear programming applied to distributed electronic power processors - Brandao, D. I.; Guillardi, H.; Pomilio, J. A.; Paredes, H. K.M. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2015)
This paper proposes a linear algorithm to optimize the compensation of reactive power, harmonic distortion and unbalanced load applied to distributed electronic power processors, for example, active power filters and/or photovoltaic grid-connected inverters, especially when their power capacity is limited. The optimized compensation consists in achieve, in terms of power quality, the best performance indices, defined at the source side and inside of a feasible region. It improves the power quality at the point of common coupling and enables full exploitation of electronic power processors, increasing their efficiency. The optimized compensation is based on the orthogonal current decomposition (Conservative Power Theory) and on the linear programming (Simplex algorithm). The steady state and dynamic behaviors have been analyzed by theoretical and simulation results. Finally, experimental results are shown to validate the proposed optimized compensation approach.
Keywords: Distributed generation; Linear programming; Microgrid; Optimized compensation; Simplex algorithm